Neuroserpin alleviates cerebral ischemia-reperfusion injury by suppressing ischemia-induced endoplasmic reticulum stress - Yumei Liao; Qinghua Zhang; Qiaoyun Shi; Peng Liu; Peiyun Zhong; Lingling Guo; Zijian Huang; Yinghui Peng; Wei Liu; Shiqing Zhang; István Adorján; Yumi Fukuzaki; et al. (Neural Regeneration Research)
Neuroserpin, a secreted protein that belongs to the serpin superfamily of serine protease inhibitors, is highly expressed in the central nervous system and plays multiple roles in brain development and pathology. As a natural inhibitor of recombinant tissue plasminogen activator, neuroserpin inhibits the increased activity of tissue plasminogen activator in ischemic conditions and extends the therapeutic windows of tissue plasminogen activator for brain ischemia. However, the neuroprotective mechanism of neuroserpin against ischemic stroke remains unclear. In this study, we used a mouse model of middle cerebral artery occlusion and oxygen-glucose deprivation/reperfusion-injured cortical neurons as in vivo and in vitro ischemia-reperfusion models, respectively. The models were used to investigate the neuroprotective effects of neuroserpin. Our findings revealed that endoplasmic reticulum stress was promptly triggered following ischemia, initially manifesting as the acute activation of endoplasmic reticulum stress transmembrane sensors and the suppression of protein synthesis, which was followed by a later apoptotic response. Notably, ischemic stroke markedly downregulated the expression of neuroserpin in cortical neurons. Exogenous neuroserpin reversed the activation of multiple endoplasmic reticulum stress signaling molecules, the reduction in protein synthesis, and the upregulation of apoptotic transcription factors. This led to a reduction in neuronal death induced by oxygen/glucose deprivation and reperfusion, as well as decreased cerebral infarction and neurological dysfunction in mice with middle cerebral artery occlusion. However, the neuroprotective effects of neuroserpin were markedly inhibited by endoplasmic reticulum stress activators thapsigargin and tunicamycin. Our findings demonstrate that neuroserpin exerts neuroprotective effects on ischemic stroke by suppressing endoplasmic reticulum stress.